2013
DOI: 10.1681/asn.2012121236
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42 Deficiency Causes Ciliary Abnormalities and Cystic Kidneys

Abstract: Ciliogenesis and cystogenesis require the exocyst, a conserved eight-protein trafficking complex that traffics ciliary proteins. In culture, the small GTPase Cdc42 co-localizes with the exocyst at primary cilia and interacts with the exocyst component Sec10. The role of Cdc42 in vivo, however, is not well understood. Here, knockdown of cdc42 in zebrafish produced a phenotype similar to sec10 knockdown, including tail curvature, glomerular expansion, and mitogen-activated protein kinase (MAPK) activation, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
75
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 63 publications
11
75
1
Order By: Relevance
“…It is not clear whether the cysts observed in the Ksp-cre mutants are in the collecting duct or the distal tubule. It is interesting to note that similar to Choi et al (2013), we did observe a decrease in cilia number in mutant collecting ducts. This cellular phenotype was not as penetrant as the defects in polarity and differentiation, suggesting that it might be a secondary manifestation of Cdc42 deletion.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…It is not clear whether the cysts observed in the Ksp-cre mutants are in the collecting duct or the distal tubule. It is interesting to note that similar to Choi et al (2013), we did observe a decrease in cilia number in mutant collecting ducts. This cellular phenotype was not as penetrant as the defects in polarity and differentiation, suggesting that it might be a secondary manifestation of Cdc42 deletion.…”
Section: Discussionsupporting
confidence: 79%
“…In conclusion, we and others have shown that Cdc42 is required for normal tubulogenesis in ureteric bud and metanephric mesenchyme development of the kidney (Choi et al, 2013;Reginensi et al, 2013). Although the morphological observations are similar in all these studies, the mechanisms proposed differ.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations